Surface properties transformation of multi-walled carbon nanotubes on reatment with various acids. - Hussein, Mohd. Zobir; Latip, Suzanita; Sarijo, Siti Halimah; Zainal, Zulkarnain (International Congress of Chemistry and Environment, 2011)
Multi-walled carbon nanotubes (MWCNTs) were treated with various acids namely nitric, citric, chromic and a mixture of nitric-sulphuric acids to introduce carboxylic acid functional groups on them. As a result of this treatment, carboxylic functional groups were found to exist as indicated by Fourier transformed infrared spectroscopy (FTIR) study. Breuneur-Emmet-Teller (BET) specific surface area of the resulting samples was found to be 98, 133, 167 and 247 m 3/g for the sample treated with a mixture of nitric and sulfuric, citric acid chromic acid and nitric acid respectively. Compared to the specific surface area of 1210 m 2/g for the starting MWCNTs, this is equivalent to percentage reduction of 91.8, 89.0, 86.2 and 79.6 % respectively. The crystallinity of the samples increased when nitric and a mixture of nitric and sulphuric acids were used for the treatment, but decreased when citric or chromic acid were used, as observed by X-ray diffraction (XRD) study. Except for the MWCNTs treated with nitric acid, diameter expansion was observed for all the samples.